(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Pratama OA, Tunjung WAS, Sutikno, Daryono BS. 2019. Bioactive compound profile of melon leaf extract (Cucumis melo L. ‘Hikapel’) infected by downy mildew. Biodiversitas 20: 3448-3453. Plants express specific secondary metabolites (phytoalexin) in response to infection. Downy Mildew which infects melon plants (Cucumis melo L. ‘Hikapel’) caused by Pseudoperonospora cubensis Rostovtsev. Hikapel is one of superior melon cultivar produced from research in the Laboratory of Genetics, Faculty of Biology, Universitas Gadjah Mada, Yogyakarta, Indonesia. Bioactive content of Hikapel melon leaf under normal condition and infected by Downy Mildew yet to be researched. This research aims to screen bioactive profile of Hikapel leaf extract that has potential as phytomedicine. Leaf extract is compared between healthy plants and infected by Downy Mildew. Dried melon leaf was powdered using mortar and pestle. Leaf powder was extracted using hexane solvent. Extract was analyzed using a Shimadzu GCMS-QP2010S. Analysis found useful compounds like phytol, methyl ricinoleate, methyl linoleate, methyl stearate, and 1-hexacosanol. with therapeutic activity such as antibacterial, antifungal, antioxidant, antiinflammatory, antidiuretic, antidiarrheal, lowering blood LDL-C level, insulin level booster, antiproliferative, and anticancer. Some bioactive compounds are only synthesized in Hikapel melon leaf under stress conditions.